2014
DOI: 10.1186/1757-7241-22-8
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive continuous versus intermittent arterial pressure monitoring: evaluation of the vascular unloading technique (CNAP device) in the emergency department

Abstract: BackgroundMonitoring cardiovascular function in acutely ill patients in the emergency department (ED) is of paramount importance. Arterial pressure (AP) is usually monitored using intermittent oscillometric measurements with an upper arm cuff. The vascular unloading technique (VUT) allows continuous noninvasive AP monitoring. In this study, we compare continuous AP measurements obtained by VUT with intermittent oscillometric AP measurements in ED patients. In addition, we aimed to investigate whether continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Studies have shown that the technology provides arterial pressure values with reasonable agreement in comparison with invasive arterial pressure measurements in anesthetized patients during surgical procedures [5][6][7], intensive care unit (ICU) patients [8,9], and emergency department patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the technology provides arterial pressure values with reasonable agreement in comparison with invasive arterial pressure measurements in anesthetized patients during surgical procedures [5][6][7], intensive care unit (ICU) patients [8,9], and emergency department patients [10].…”
Section: Introductionmentioning
confidence: 99%
“…blood transfusions, vasopressor infusions) depending on the BP monitoring method used. Besides these inaccuracies concerning BP measurements, the treating physician should be aware that clinically relevant hypotensive episodes might be missed or detected late by oscillometric versus continuous beat-to-beat BP [45]. The lack of adequate oscillometric BP validation studies and their demonstrated shortcomings should lead to reconsidering the confidence in oscillometric BP.…”
Section: A N U S C R I P Tmentioning
confidence: 94%
“…The CNAP system improved the detection of fast BP changes in patients receiving sedating agents during interventional endoscopy [59]. Further, it has high potential to improve patient safety during caesarian section [60] and in acutely ill patients admitted to the emergency room [45] -clinical scenarios in which arterial cannulation is not clearly indicated or challenging.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Continuous ECG was recorded simultaneously with the neurogram using a bioamp system. Beat-to-beat arterial BP was measured noninvasively using finger cuffs that detect digital blood flow and translate blood flow oscillations into continuous pulsepressure waveforms and beat-to-beat values of BP (CNAP, CNSystems) (20,46,47,52,55). Absolute values of BP were internally calibrated using a concomitant upper arm BP reading and were calibrated at the start and every 15 min throughout the study.…”
Section: Measurements and Proceduresmentioning
confidence: 99%